Teori HudÃ»d Muhammad Syahrur dan Kontribusinya dalam Penafsiran Al-Qurâ€™an - Mustaqim, Abdul (AL QUDS : Jurnal Studi Alquran dan Hadis, 2017)
One of the great thinkers in the contemporary era is Muhammad SyahrÃ»r, a Syrian liberal Islamic figure. Through his controversial works, al-KitÃ¢b wal Qurâ€™Ã¢n: QirÃ¢â€™ah Mu`Ã¢shirah, (al-Kitab and al-Qurâ€™an: a Contemporary Reading) Syahrur introduces a new theory of Quranic interpretation, called as the theory of limits. He asserts that the theory of limits is an approach within ijtihad (individual interpretation) to study the muhkamÃ¢t verses (clear and direct verses of law) of the Qurâ€™an. The term limit (hudÃ»d) used by Shahrur refers to the meaning of â€œthe bounds or restrictions of God which should not be violated, contained in the dynamic, flexible, and elastic domain of ijtihad.â€. By using the descriptive-analytical method, the article is talking about the contribution of the theory of limits in qurâ€™anic interpretation that makes significant contributions to the enhancement of Qurâ€™anic studies.